Probing thermal interactions of ionic liquids with dimethyl sulfoxide - Rai, Gitanjali; Kumar, Anil (Chemphyschem, 2012)
Interactions between ionic liquids and dimethyl sulfoxide (DMSO) are probed by isothermal titration calorimetry. The excess partial molar enthalpies of ionic liquids H-IL(E) in DMSO are discussed in terms of solutesolvent interactions. The specific interaction theory originally developed by Pitzer is used to analyze the apparent molar enthalpy phi(L) of ionic liquids in DMSO with the help of ion-interaction parameters. Furthermore, quantitative information on solvent reorganization and clathrate formation is obtained and interpreted.
Keywords: calorimetry; dimethyl sulfoxide; ionic liquids; solvent effects; thermochemistry